1978
DOI: 10.1111/j.1651-2227.1978.tb16292.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Infant Death in Copenhagen 1956–1971

Abstract: 131 cases of the Sudden Infant Death Syndrome (SIDS) in the municipality of Copenhagen 1956--71 (incidence 0.92 SIDS cases per 1 000 live births) were investigated on the basis of police reports and infant health visitor's records. Fewer SIDS cases were breast-fed than controls from the second week of life to four months of age. No significant differences were found with respect to the concentrations of fresh cow's milk dilutions, age at introduction of solid food, or number of meals per day. From 1956 to 1971… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…This is consistent with the findings of Biering-Sørensen and colleagues, who found no rise in the incidence of SIDS accompanying an increase in artificial feeding in Copenhagen between 1956 and 1971. 4 The fall in SIDS incidence after 1991 was caused by abandonment of prone as the preferred sleeping position, in turn promoted by the risk reducing campaigns. 8 18 We have estimated the duration of breast feeding, exclusive and non-exclusive, in weeks and used these as measures of breast feeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the findings of Biering-Sørensen and colleagues, who found no rise in the incidence of SIDS accompanying an increase in artificial feeding in Copenhagen between 1956 and 1971. 4 The fall in SIDS incidence after 1991 was caused by abandonment of prone as the preferred sleeping position, in turn promoted by the risk reducing campaigns. 8 18 We have estimated the duration of breast feeding, exclusive and non-exclusive, in weeks and used these as measures of breast feeding.…”
Section: Discussionmentioning
confidence: 99%
“…There is still controversy as to whether bottle feeding is an independent risk factor or not. In Copenhagen, Biering-Sørensen and colleagues 4 described an increase in artificial feeding through the years 1956-71 but no accompanying rise in the incidence of SIDS, as would be expected from a causal association. The New Zealand study 8 9 showed an independent effect of breast feeding, with an odds ratio of 2.9 (95% CI: 1.8 to 4.7), but in England 10 11 and Scotland 12 this was not found.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…16,18,31,49,[89][90][91][92][93][94][95][96][97][98] Although some studies show a protective effect of breastfeeding on SIDS, 18,98,99 others do not. 31,49,91,96,97,100,101 In addition, a recent article has demonstrated that although breastfeeding is associated with decreased postneonatal deaths overall, it is not associated with a reduced risk of SIDS. 102 Many of the case-control studies demonstrate a protective effect of breastfeeding against SIDS in univariate analysis but not when confounding factors are taken into account.…”
Section: Relationship Between Breastfeeding and Sidsmentioning
confidence: 99%
“…However, epidemiologic studies have been inconsistent in showing a protective effect of breastfeeding on the risk of SIDS; some study results have supported a protective effect, [5][6][7][8][9][10][11] and others have not. 2,5,8,[12][13][14][15][16][17][18][19] The authors of a meta-analysis and qualitative literature review published in 2000 concluded that there was a statistically significant increase in SIDS risk for bottle-fed infants. 20 These authors, however, defined SIDS loosely (as any sudden and unexplained death in an infant or young child) and included studies in which the definitions of breastfeeding exposure differed, and there were other methodologic flaws.…”
mentioning
confidence: 99%